2019
DOI: 10.1017/s1431927619015034
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Carbon Electrodes for In Situ Redox Studies in a Transmission Electron Microscope

Abstract: Electrochemical liquid cell transmission electron microscopy (TEM) is a unique technique for probing nanocatalyst behavior during operation for a range of different electrocatalytic processes, including hydrogen evolution reaction (HER), oxygen evolution reaction (OER), oxygen reduction reaction (ORR), or electrochemical CO2 reduction (eCO2R). A major challenge to the technique's applicability to these systems has to do with the choice of substrate, which requires a wide inert potential range for quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 55 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…In the corresponding FFT (Figure 1b)the d-spacing is assigned to Cu {111} planes, which confirms their metallic nature.F igure 1c then depicts the electrochemical chip design adopted specifically for the in situ CO 2 RR TEM experiments.T he ability to perform CO 2 RR inside the confined volume of the micro-cells used for in situ TEM demands the suppression of the hydrogen evolution reaction and the elimination of the intrinsic activity of the supporting electrode for CO 2 RR. [29,30] These requirements rule out the use of typical metals used for current collectors in micro-cells,s uch as platinum or gold. Glassy carbon or carbon felt is typically used as the supporting electrode for CO 2 RR nanoparticle catalysts due to its good conductivity,l ow chemical reactivity,l arge overpotential for HER and minimal activity for CO 2 RR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the corresponding FFT (Figure 1b)the d-spacing is assigned to Cu {111} planes, which confirms their metallic nature.F igure 1c then depicts the electrochemical chip design adopted specifically for the in situ CO 2 RR TEM experiments.T he ability to perform CO 2 RR inside the confined volume of the micro-cells used for in situ TEM demands the suppression of the hydrogen evolution reaction and the elimination of the intrinsic activity of the supporting electrode for CO 2 RR. [29,30] These requirements rule out the use of typical metals used for current collectors in micro-cells,s uch as platinum or gold. Glassy carbon or carbon felt is typically used as the supporting electrode for CO 2 RR nanoparticle catalysts due to its good conductivity,l ow chemical reactivity,l arge overpotential for HER and minimal activity for CO 2 RR.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 c then depicts the electrochemical chip design adopted specifically for the in situ CO 2 RR TEM experiments. The ability to perform CO 2 RR inside the confined volume of the micro‐cells used for in situ TEM demands the suppression of the hydrogen evolution reaction and the elimination of the intrinsic activity of the supporting electrode for CO 2 RR [29, 30] . These requirements rule out the use of typical metals used for current collectors in micro‐cells, such as platinum or gold.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, amorphous, glassy carbon (GC) electrodes have been shown to be excellent candidates. When we tested the electrochemically inert window for customized or commercial GC electrodes, we found them to be an adequate choice for many electrocatalysts studies, including the CO 2 ER at low potential, the ORR, and the OER, and under alkaline, neutral, or acidic conditions (Figure g). , We note that these electrodes show a typically increased resistivity (and hence a higher ohmic drop) and that owing to the difficulties of pretreating GC electrodes in the ec-LPTEM apparatus, there are often increased resistances that are attributed to slow charge-transfer rates at the electrolyte–electrode interface. , Additionally, we have found them to be highly fragile and they can withstand only limited reaction times in the highly negative potential ranges …”
Section: Electrocatalytic Measurements In Tem Microcellsmentioning
confidence: 99%
“…The simulation results indicated that a uniform current distribution was observed when the ratio of the square of the coplanar electrode width to the cell height was greater than 5 . Recently, in order to acquire a wide inert potential window for quantitative electrochemical measurement in the catalytic process, Girod et al proposed a feasible electrochemical setup using carbon coated electrode . Through a series of cyclic voltammetry studies of the influence factors using the standard ferrocyanide/ferricyanide redox couple, the authors demonstrated the setup has the capability to detect several electrocatalytic systems, and the measured potential was related to the bulk system.…”
Section: Advanced Combination Of Multitechniques In a Confined Spacementioning
confidence: 99%